Caught in the cycle: Economic conditions at enrollment and labor market outcomes of college graduates - Alena Biécáková; Guido Matias Cortes; Jacopo Mazza (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2020)
We find robust evidence that cohorts of graduates who enter college during worse economic times earn higher average wages than those who enter during better times. This difference is not explained by differences in economic conditions at the time of college graduation, changes in field of study composition, or changes in selection into occupations or industries. Cohorts who start college in bad times are not more positively selected based on their high-school outcomes, but they graduate with higher college grades, and earn higher wages conditional on their grades. Our results suggest that these cohorts exert more effort during their studies.
Keywords: I23; J24; J31; E32; 330; Business Cycle; Higher Education; Cohort Effects